Cover Image. (15th April 2020) - Eigentler, Thomas Wilhelm; Winter, Lukas; Han, Haopeng; Oberacker, Eva; Kuehne, Andre; Waiczies, Helmar; Schmitter, Sebastian; Boehmert, Laura; Prinz, Christian; Trefna, Hana Dobsicek; Niendorf, Thoralf
Abstract : The cover image is based on the Research Article Wideband Self–Grounded Bow–Tie Antenna for Thermal MR at 7.0 Tesla by Thomas Wilhelm Eigentler et al., https://doi.org/10.1002/nbm.4274 .